Preparation method of iron-aluminum porous material
By using the high-temperature decomposition of anhydrous magnesium carbonate and the Kirkendal effect between iron and aluminum in the iron and aluminum porous material, the problems of high porosity and grain enlargement in the prior art were solved, and excellent results were prepared Porous materials with high temperature performance and long service life.
Patent Information
- Application Number
- CN202411299749.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to prepare porous materials with high porosity, short preparation period and able to inhibit the increase of grains of intermetallic compounds in iron and aluminum, and cannot meet the requirements of high temperature filtration and service life.
Iron powder, aluminum powder and anhydrous magnesium carbonate powder are mixed under vacuum or inert gas protection, and pores are made through the high-temperature decomposition of anhydrous magnesium carbonate and the Kirkendal effect between iron and aluminum to form iron with high porosity iron. A porous material of aluminum intermetallic compounds, which uses magnesium oxide to inhibit grain growth.
The preparation of porous materials with high porosity is achieved, which extends the service life and ensures excellent high-temperature performance, corrosion resistance and oxidation resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the field of alloy materials, in particular to a method for preparing an iron-aluminum porous material. Background Art
[0002] Intermetallic compound porous materials are special materials among porous materials. Due to the covalent bonds and metallic bonds in the crystal structure, they have the advantages of both metals and ceramics, and overcome the shortcomings of poor high-temperature performance of traditional metal porous materials and poor toughness and weldability of traditional ceramic porous materials. They have the advantages of low density, good high-temperature mechanical properties, good corrosion resistance, good oxidation resistance and good sulfidation resistance. Iron and aluminum elements are highly abundant on the earth, easy to obtain, and low in price, and the iron-aluminum intermetallic compounds formed by the two have the above advantages. Modern industries such as steel, coal power, cement and other industries will produce a large amount of high-temperature smoke and corrosive exhaust gas in production activities, which seriously affect the environment and people's normal life. How to filter and treat these pollutants has become a top priority. Traditional metal porous materials have poor high-temperature oxidation and sulfurization resistance and cannot meet the filtration requirements under high temperatures. Porous ceramic materials are highly brittle and have poor seismic resistance. They will be damaged by thermal stress during use, affecting production safety and service life. Therefore, utilizing the excellent high-temperature mechanical properties and corrosion, oxidation and sulfurization resistance of iron-aluminum intermetallic compound porous materials to prepare porous iron-aluminum intermetallic compound materials with an open-pore structure for high-temperature filtration is an effective method to solve the problem of high-temperature exhaust gas treatment.
[0003] The preparation methods of porous materials of iron-aluminum intermetallic compounds mainly include reaction synthesis method and pore-forming agent method. Reaction synthesis method is a common method for preparing porous materials of metal compounds. Its principle is to use the Kirkendall effect caused by different diffusion coefficients between different metal elements to form pores. The advantage is that the process is simple and no pore-forming agent is required. However, the disadvantage is that the preparation cycle of this method is long, and the porosity of the prepared porous materials is generally not high, usually around 50%. The pore-forming agent sintering method is another relatively mature preparation process. A certain proportion of iron-aluminum metal powder and inorganic or organic pore-forming agent are mixed, and the pore-forming agent is removed by a suitable method before or during sintering to achieve pore formation. The advantage of this method is that the porosity and pore size of the porous material can be adjusted by controlling the morphology, size and content of the pore former, but this method cannot produce porous materials with high porosity. The reason is that if the proportion of the pore former is too large, the sample will collapse and deform after the pore former is removed. In addition, the pore former may react with the iron and aluminum elements in the matrix in a solvent environment or a high temperature environment and cannot be completely removed, thus affecting the performance of the final product. In addition, the high temperature use environment will cause the grain size of the iron-aluminum intermetallic compound porous material to increase, affecting its service life. Therefore, it is of great significance to prepare a porous iron-aluminum intermetallic compound material with high porosity, short preparation cycle, and effective inhibition of the increase of intermetallic compound grains. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing an iron-aluminum porous material.
[0005] To solve the above problems, the present invention adopts the following technical solutions.
[0006] A method for preparing an iron-aluminum porous material comprises mixing iron powder, aluminum powder and anhydrous magnesium carbonate powder under vacuum or inert gas protection to obtain a uniform Fe-Al-MgCO3 ternary mixed powder, pressing the ternary mixed powder into a shape and then vacuum sintering it.
[0007] The purpose of the present invention is to provide a new method for efficiently preparing porous iron-aluminum intermetallic compound materials by utilizing the diffusion / reaction pore formation of iron powder and aluminum powder during the sintering process and the high-temperature decomposition pore formation of magnesium carbonate during the sintering process. This method synergistically utilizes the following two approaches to improve the porosity of porous iron-aluminum intermetallic compound materials: 1) High-temperature decomposition of anhydrous magnesium carbonate. Under high-temperature conditions, anhydrous magnesium carbonate will decompose into magnesium oxide and carbon dioxide. Carbon dioxide can escape under vacuum conditions to achieve gas phase removal and pore formation. In addition, the dispersed magnesium oxide can inhibit the grain growth of the iron-aluminum intermetallic compound, ensuring the excellent high-temperature performance of the porous material; 2) The Kirkendall effect between iron and aluminum. Since iron and aluminum, two metals with different diffusion rates, will form defects during the diffusion process, and micropores will be formed at the defects.
[0008] The principle of the present invention is that in a ternary Fe-Al-MgCO3 system, at 500-600°C, anhydrous magnesium carbonate will undergo high-temperature decomposition to produce magnesium oxide and carbon dioxide, and the carbon dioxide will escape rapidly under a high-temperature vacuum environment, thereby achieving the decomposition, removal and pore formation of magnesium carbonate, and improving the porosity while removing magnesium carbonate. The magnesium oxide formed by the decomposition of magnesium carbonate will be dispersed in the matrix of the intermetallic compound porous material, inhibiting the growth of the intermetallic compound grains, forming a nano-MgO-enhanced iron-aluminum intermetallic compound porous material, increasing the service life of the porous material, and ensuring excellent high-temperature performance. At the same time, at 500-600°C, solid-state diffusion and reaction occur between iron and aluminum, further improving the porosity, and the generated micropores will provide escape channels for the carbon dioxide generated by the decomposition of anhydrous magnesium carbonate.
[0009] In addition, the melting point of aluminum is about 660°C. When the temperature of the ternary system rises to 660-700°C, aluminum will become liquid and react rapidly with the surrounding iron particles to generate a series of iron-aluminum intermetallic compounds. The Kirkendall effect between the iron and aluminum elements further increases the porosity. Finally, it is further sintered at high temperature to achieve uniform composition and obtain a single iron-aluminum intermetallic compound porous material.
[0010] It can be seen from the Fe-Al binary phase diagram that aluminum and iron will form a series of iron-aluminum intermetallic compounds, such as FeAl, FeAl2, Fe2Al5, FeAl3 and Fe3Al, etc. Preferably, in the initial composition ratio of the Fe-Al-MgCO3 ternary mixed powder system, iron powder, aluminum powder and anhydrous magnesium carbonate are mixed according to the ratio of (Fe-xAl)-yMgCO3, x, y are both atomic percentages, x ranges from 22.5% to 76.5%, and y ranges from 30% to 60%. According to the above atomic percentages, the weights of iron powder, aluminum powder and anhydrous magnesium carbonate powder are calculated respectively, and the ternary mixed powder is weighed and configured.
[0011] Preferably, in the ternary mixed powder, the particle size of the iron powder is 0.1 to 300 μm, the particle size of the aluminum powder is 0.1 to 300 μm, and the particle size of the anhydrous magnesium carbonate powder is 0.1 to 300 μm.
[0012] Preferably, the ternary mixed powder is formed by conventional compression molding or cold isostatic pressing, and the compression molding pressure is greater than 100 MPa.
[0013] Preferably, the vacuum degree of the vacuum sintering should be less than 0.01Pa.
[0014] Preferably, the vacuum sintering is performed using a multi-stage heating and heat preservation process.
[0015] Preferably, the vacuum sintering comprises the following steps:
[0016] (1) After the uniformly mixed Fe-Al-MgCO3 ternary powder is pressed into shape, it is placed in a tubular sintering furnace for vacuum sintering, and the temperature is raised to the anhydrous magnesium carbonate decomposition temperature zone at a heating rate of 1°C / min to 10°C / min and kept warm for 1 to 5 hours; the temperature range of the anhydrous magnesium carbonate decomposition temperature zone is 500 to 600°C, which is also the temperature range of the iron-aluminum solid-state reaction; specifically, in this step (1), different temperature points can be selected in the decomposition temperature zone for different insulation times according to the different proportions of MgCO3 powder and the different ratios of the iron and aluminum binary components in the Fe-Al-MgCO3 ternary system; the main purpose of heating and insulation at this stage is to fully decompose the anhydrous magnesium carbonate powder, generate carbon dioxide gas and escape it, generate a large number of pores in the matrix, and at the same time, allow the magnesium oxide generated by the decomposition of the anhydrous magnesium carbonate to be fully dispersed into the matrix.
[0017] (2) Continue to heat the sintered billet at a rate of 1°C / min to 10°C / min to a temperature above the melting point of aluminum, which is generally 660°C to 700°C, and keep the temperature within this range for 1 to 4 hours; the remaining aluminum in the solid state is completely transformed into liquid aluminum, and the residual liquid aluminum quickly reacts with the surrounding iron particles to generate a series of iron-aluminum intermetallic compounds. This process ensures that there is no single aluminum in the sintered billet and further increases the porosity.
[0018] (3) Continue heating to 900-1100°C at a heating rate of 1°C / min-10°C / min (the specific temperature is determined according to the composition of the iron-aluminum intermetallic compound), and keep it at this temperature for 1-2 hours. The heating and keeping in this temperature range will complete the high-temperature phase transformation, generate the expected iron-aluminum intermetallic compound and complete the composition homogenization. The open porosity of the iron-aluminum intermetallic compound porous material finally obtained can reach more than 60%, the total porosity can reach more than 65%, and the pore size range is 1-100 μm.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) In the low-temperature stage, solid-state diffusion / reaction of iron and aluminum elements is used to form pores. The pores formed in this stage can serve as escape channels for carbon dioxide, a decomposition product of anhydrous magnesium carbonate, which is conducive to the complete escape of gas and increases the open porosity.
[0021] (2) The present invention makes full use of the thermal decomposition property of anhydrous magnesium carbonate to form carbon dioxide gas through high-temperature decomposition. The escape of the gas is beneficial to the preparation of a porous iron-aluminum intermetallic compound material with high open porosity.
[0022] (3) Magnesium oxide, the decomposition product of anhydrous magnesium carbonate, can be dispersed in the sintered blank. The dispersed magnesium oxide can inhibit the grain growth of the iron-aluminum intermetallic compound, which is beneficial to prolong the service life of the iron-aluminum intermetallic compound porous material and ensure the safety of production activities. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are clearly and completely described below; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] Embodiment 1 of the present invention provides a method for preparing a porous iron-aluminum intermetallic compound material, which specifically comprises the following steps:
[0026] (1) Select three powders of elemental iron powder, elemental aluminum powder and anhydrous magnesium carbonate powder as the original powders, and their particle sizes are all 30 μm. According to the atomic ratio of ((Fe-50%Al)-30% MgCO3), the weights of the three powders are calculated and the powders are weighed to obtain the iron-aluminum intermetallic compound porous material with the designed composition of B2-FeAl. Then, mix the materials in a vacuum mixing tank for 6 hours, and finally mold the uniformly mixed ternary powder at a pressure of 200 MPa.
[0027] (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 500°C at a rate of 5°C / min and kept at this temperature for 2 hours. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solid solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores. In addition, anhydrous magnesium carbonate will decompose under heat at 500°C to generate magnesium oxide and carbon dioxide. Carbon dioxide can escape through the pores generated by the iron-aluminum reaction and further increase the porosity.
[0028] (3) Continue to heat up to 660°C at a heating rate of 1°C / min and keep the temperature for 1 hour. At this time, the remaining solid aluminum in step (2) will all become liquid, and the residual liquid aluminum will quickly react with the surrounding iron particles and be completely consumed. At this stage, the positions originally occupied by aluminum particles will all become pores, and the porosity will be further improved.
[0029] (4) The temperature is continued to be raised to 950°C at a heating rate of 5°C / min and kept at this temperature for 2 h. During this stage, the porosity is increased by further diffusion / reaction between iron and aluminum, and the high-temperature phase transition is completed to achieve composition homogenization. Finally, a B2-FeAl intermetallic compound porous material consistent with the designed composition is obtained, and the open pore ratio is 60% and the total porosity is 65%.
[0030] Example 2
[0031] Embodiment 2 of the present invention provides a method for preparing a porous iron-aluminum intermetallic compound material, which specifically comprises the following steps:
[0032] (1) Select three powders of elemental iron powder, elemental aluminum powder and anhydrous magnesium carbonate powder as the original powders, and their particle sizes are all 60 μm. According to the atomic ratio of ((Fe-67%Al)-50% MgCO3), the weights of the three powders are calculated and the powders are weighed to obtain the iron-aluminum intermetallic compound porous material with the designed composition of FeAl2. Then, mix the materials in a vacuum mixing tank for 8 hours, and finally mold the uniformly mixed ternary powder at a pressure of 200 MPa.
[0033] (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 550°C at a rate of 8°C / min and kept at this temperature for 2 hours. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solid solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores. In addition, anhydrous magnesium carbonate will decompose under heat at 550°C to generate magnesium oxide and carbon dioxide. Carbon dioxide can escape through the pores generated by the iron-aluminum reaction and further increase the porosity.
[0034] (3) Continue to heat up to 680°C at a heating rate of 1°C / min and keep the temperature for 1 hour. At this time, the remaining solid aluminum in step (2) will all become liquid, and the residual liquid aluminum will quickly react with the iron particles around it and be completely consumed. At this stage, the positions originally occupied by aluminum particles will all become pores, and the porosity will be further improved.
[0035] (4) Continue to heat the material to 1000°C at a heating rate of 8°C / min and keep the temperature for 1.5 h. In this stage, the porosity is increased by further diffusion / reaction between iron and aluminum, and the high-temperature phase transition is completed to achieve composition homogenization. Finally, a porous FeAl2 intermetallic compound material with the same design composition is obtained, with an open pore ratio of 65% and a total porosity of 70%.
[0036] Example 3
[0037] Embodiment 3 of the present invention provides a method for preparing a porous iron-aluminum intermetallic compound material, which specifically comprises the following steps:
[0038] (1) Select three powders of elemental iron powder, elemental aluminum powder and anhydrous magnesium carbonate powder as the original powders, and their particle sizes are all 80 μm. According to the atomic ratio of ((Fe-25%Al)-60% MgCO3), the weights of the three powders are calculated and the powders are weighed to obtain the iron-aluminum intermetallic compound porous material with the designed composition of Fe3Al. Then, mix the materials in a vacuum mixing tank for 10 hours, and finally mold the uniformly mixed ternary powder at a pressure of 200 MPa.
[0039] (2) The pressed green sheet is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 600°C at a rate of 10°C / min and kept at this temperature for 2 hours. Since the intrinsic diffusion coefficient of aluminum is much larger than that of iron, aluminum atoms will continue to diffuse to the surrounding iron particles at this stage. The aluminum atoms diffused to the iron particles will first dissolve into the iron. When the aluminum atoms reach the solid solubility limit in the iron matrix, aluminum reacts with iron (aluminum) to form a series of intermetallic compounds. A large number of vacancies will be formed around the aluminum particles at this stage, and the aggregation of vacancies will form pores. In addition, anhydrous magnesium carbonate will decompose under heat at 600°C to generate magnesium oxide and carbon dioxide. Carbon dioxide can escape through the pores generated by the iron-aluminum reaction and further increase the porosity.
[0040] (3) Continue to heat up to 700°C at a heating rate of 2°C / min and keep warm for 1 hour. At this time, the remaining solid aluminum in step (2) will all become liquid, and the residual liquid aluminum will quickly react with the surrounding iron particles and be completely consumed. At this stage, the positions originally occupied by aluminum particles will all become pores, and the porosity will be further improved.
[0041] (4) Continue to heat the material to 1100°C at a heating rate of 10°C / min and keep the temperature for 1 hour. During this stage, the porosity is increased by further diffusion / reaction between iron and aluminum, and the high-temperature phase transition is completed to achieve composition homogenization. Finally, a Fe3Al intermetallic compound porous material with the same design composition is obtained, and the open pore ratio is 68% and the total porosity is 70%.
[0042] The above is only a preferred specific implementation of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an iron-aluminum porous material, characterized in that: The specific steps include: S1 selects three kinds of powders, namely, elemental iron powder, elemental aluminum powder and anhydrous magnesium carbonate powder, as raw powders, then mixes the powders in a vacuum mixing tank, and finally molds the uniformly mixed three-element powders; S2: The pressed green sheet is placed in a tubular furnace for vacuum sintering. First, the temperature is raised to 500-600℃ at a rate of 5-10℃ / min and kept at this temperature for 2h. In this stage, a large number of vacancies will be formed around the aluminum particles, and the aggregation of vacancies will form pores. Anhydrous magnesium carbonate will be decomposed by heat at 500℃ to generate magnesium oxide and carbon dioxide. The carbon dioxide can escape through the pores generated by the iron-aluminum reaction and further increase the porosity. S3 continues to heat up to 660-700℃ at a heating rate of 1-2℃ / min and keeps warm for 1h. At this time, the remaining solid aluminum in S2 will all turn into liquid, and the residual liquid aluminum will quickly react with the iron particles around it and be completely consumed; at this stage, the positions originally occupied by aluminum particles will all turn into pores, and the porosity will be further improved; S4 continues to heat up to 950-1100℃ at a heating rate of 5-10℃ / min and keeps warm for 2h. In this stage, the porosity is increased by further diffusion / reaction between iron and aluminum, and the high-temperature phase transition is completed to achieve composition homogenization, and finally a B2-FeAl intermetallic compound porous material consistent with the designed composition is obtained.
2. The method for preparing an iron-aluminum porous material according to claim 1, characterized in that: In the ternary mixed powder, the particle size of the iron powder is 0.1 to 300 μm, the particle size of the aluminum powder is 0.1 to 300 μm, and the particle size of the anhydrous magnesium carbonate powder is 0.1 to 300 μm.
3. The method for preparing an iron-aluminum porous material according to claim 1, characterized in that: The ternary mixed powder is formed by conventional compression molding or cold isostatic pressing, and the compression molding pressure is greater than 100 MPa.
4. The method for preparing an iron-aluminum porous material according to claim 1, characterized in that: The vacuum degree of the vacuum sintering should be less than 0.01Pa.
5. The method for preparing an iron-aluminum porous material according to claim 1, characterized in that: The vacuum sintering is carried out in a multi-stage heating and heat preservation process.
Citation Information
Cited By
Preparation method of iron-aluminum hierarchical porous material
CN119870469A
Preparation method of an iron-aluminum-based hierarchical porous material
CN119870469B
